Propriedade intelectual e Teoria Social Crítica: caso do aprimoramento de sementes e dos direitos dos agricultores - Salum, Gabriel Cunha [UNESP] (2015)
The use of intellectual property paradigm is based on an institutionalized logic control of knowledge that generates wealth and power for certain social actors and, simultaneously and paradoxically imposes or aggravates poverty and subordination to others. Against legal-economic and technological constraints that limit capacity and potential for human development, social movements fighting for recognition of rights linked to personal identity and collective forms of life. This study aims to analyze critically the face of this ambivalent and conflicted dynamics, investigating the case of the link between intellectual property, seeds improvement and farmers' rights in the contemporary world. Therefore, this study refers to new models of critical social theory as theoretical framework, specifically Jürgen Habermas's procedural-paradigm of the law and the concepts of legal and social recognition based on the Axel Honneth's theory of recognition, adopting as a research technique the realization of literature review of relevant national and international literature. The specific objectives of this study is to describe and to justify the applicability of theoretical and methodological framework adopted for the analysis proposed, as well as based description and critical discussion of the study subject. In the final considerations, this study confirms the hypothesis that the improvement of agricultural biotechnology and disputes over seeds today are closely related to the increasing expansion of the paradigm of intellectual property, generating social implications and conflicts of different nature. However, the study also shows that the international regime of intellectual property is not simply shaped and operated by developed countries and the lobby of large multinational companies as its operating dynamics involves negotiations and complex interests with the participation and non-participation by several states. Finally, considering the ...